Developing Students' Tendency, Motivation, and Confidence in Learning Arabic Language - Iwan Pranata (International Islamic Schools Alliance, 2020)
Language is one of communication tools between people to other people. In education activity, it's known that Arabic language is taught in some institutions and Islamic colleges only for understanding books written in Arabic scripts. In its development history until now, Arabic language has been a curriculum at several schools and colleges as a subject that helps to understand texts with Arabic language. It also works as a medium, knowledge, and insight developed in this recent era. This research aims to explain the borders of Arabic language teaching in an Islamic elementary school, and one of these schools is Islamic elementary school Al-Azhar Cairo Palembang which uses that language so their students can be noble man, and have high technology understanding. This school also use Al-Azhar’s noble curriculum and apply it to make class’s atmosphere more interesting and positive for learning Arabic language and increase students’ tendency to Arabic language learning as well as their motivation and confidence. The data collected in this research was taken from direct face to face interview with the teachers and students. Some of factors which cause Arabic language learning difficult are not coming from Arabic language itself (Arabic language system as internal factors), but also from its physiological factors (like; tendency, motivations, and the absent of confidence), as well as cultural and sociological factors. Thus, there’s necessity to use such a proper curriculum and method for learning Arabic language based on students’ psychological factors. Also, it’s because of the system of Arabic language teaching is not sure. The conclusion of this paper based on those different problems shows that it’s a necessity to prepare an educational curriculum, good teachers’ effectiveness, suitable teaching method and interesting language based environment to face and answer some Arabic language teaching’s challenges especially for non-native Arabic speaker.